1977
DOI: 10.1021/ja00454a034
|View full text |Cite
|
Sign up to set email alerts
|

Structure of 7-methyl-8-azaadenine. A crystallographic and molecular orbital study

Abstract: The crystal and molecular structure of 7-methyl-8-azaadenine (6-amino-7-niethyl-8-azapurine), CzH6N6, has been determined from three-dimensional x-ray counter data obtained using Mo Ka radiation. The material crystallizes in the orthorhombic space group Pbcn with eight formula units in a cell of dimensions a = 7.578 (2), b = 13.328 (3), and c = 12.566 ( 4 ) A. The observed and calculated densities are 1 .57 (3) and 1.572 g cmW3, respectively. The structure has been refined to a final value of the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Table 1 lists the gas-phase most relevant geometric parameters for the tautomers calculated here. The derived structural parameters compare well with those reported for 7-methylazaadenine 21 with rms deviations of ca 0.04 Å for the bond lengths and 1.2-5.2°for bond angles. The average N7-N8 and N8-N9 distances for all three tautomeric forms are 1.287 and 1.304 Å , i.e.…”
supporting
confidence: 77%
“…Table 1 lists the gas-phase most relevant geometric parameters for the tautomers calculated here. The derived structural parameters compare well with those reported for 7-methylazaadenine 21 with rms deviations of ca 0.04 Å for the bond lengths and 1.2-5.2°for bond angles. The average N7-N8 and N8-N9 distances for all three tautomeric forms are 1.287 and 1.304 Å , i.e.…”
supporting
confidence: 77%
“…Our calculation indicated that the S 0 state of all the aza analogues had a planar molecular structure as well as the corresponding normal bases. The molecule structures of 7-methyl-8-azaadenine, 8AA monohydrated, and 6AU were reported to be planar by the X-ray structure analysis.…”
Section: Resultsmentioning
confidence: 99%